Key concepts in sociology - Braham, Peter; Sage eBooks (London : SAGE, 2013)
Sociology consists of a myriad of frequently confusing concepts. This book provides a comprehensive, lively and clearly-written guide to the most important concepts in the subject. It includes both what might be regarded as 'classic' sociological concepts, such as class, bureaucracy and community, as well as subjects that have become increasingly prominent in recent times, such as celebrity, risk and the body.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Sociology; Electronic books